2019
DOI: 10.1021/acsami.9b07749
|View full text |Cite
|
Sign up to set email alerts
|

A 4 × 4 cm2 Nanoengineered Solid Oxide Electrolysis Cell for Efficient and Durable Hydrogen Production

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 56 publications
(111 reference statements)
2
59
0
Order By: Relevance
“…The reasons for the improved durability on the CGO modified Ni/YSZ electrode here should be similar to the findings in our previous work (where the CGO was introduced into the Ni/YSZ electrode after the "two-atmosphere-reduction"), i.e., mitigating microstructural deterioration including Ni migration and disconnection between Ni and YSZ at the TPBs seen on nonmodified Ni/YSZ electrodes. 12,23 After steam electrolysis, the infiltrated cell was further investigated for reversible operation under a current density of first +/−0.50 and then +/−1.00 A cm −2 at 750 °C (Fig. 9a).…”
Section: Performance At Open Circuit Voltage (Ocv) Conditions-to Evaluate the Effect Of "One-mentioning
confidence: 99%
“…The reasons for the improved durability on the CGO modified Ni/YSZ electrode here should be similar to the findings in our previous work (where the CGO was introduced into the Ni/YSZ electrode after the "two-atmosphere-reduction"), i.e., mitigating microstructural deterioration including Ni migration and disconnection between Ni and YSZ at the TPBs seen on nonmodified Ni/YSZ electrodes. 12,23 After steam electrolysis, the infiltrated cell was further investigated for reversible operation under a current density of first +/−0.50 and then +/−1.00 A cm −2 at 750 °C (Fig. 9a).…”
Section: Performance At Open Circuit Voltage (Ocv) Conditions-to Evaluate the Effect Of "One-mentioning
confidence: 99%
“…[9] Tong et al reported a degradation rate of 0.024 V kh -1 in a 900 h test at 1 A cm -2 3 with nano-engineered electrodes, which was reported to be superior to the degradation rate of most previously studied SOECs. [10] Extensive studies have been devoted to the degradation modes of all-ceramic SOECs. Electrolyte reduction, [11,12] delamination, [13,14] intergranular fracture and void formation along the grain boundaries of the electrolyte, [15] structure damage in thick yttria-stabilized zirconia (YSZ) electrolyte, [16] and formation of an insulating layer between the buffer layer and the electrolyte [17] all have been reported to degrade the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of Ni/YSZ fuel electrode with CGO electrocatalysts was performed by a prereduction procedure followed by the infiltration of Ce0.8Gd0.2O2-δ (CGO20) nitrate precursor solution containing stoichiometric amounts of Ce(NO3)3 and Gd(NO3)3 (4:1 molar ratio to metal ions), as previously reported. 29 The infiltration processes were repeated 7 times to get a loading of ∼110 mg CGO20 per 1 cm 3 Ni/YSZ structure (Ni/YSZ fuel electrode + Ni/YSZ support).…”
Section: Fabrication Of Fuel-electrode-supported Cellsmentioning
confidence: 99%
“…53 Recently, encouraging progress has been made in understanding the degradation mechanism and in strategies to reduce degradation. 29,45,46,54,55 We have found that surface modification of the Ni/YSZ electrode by coating nano-sized Ce0.8Gd0.2O2-δ (CGO20) electrocatalysts is an effective approach to enhance the cell durability. 29,45,56 Here, we applied this approach to the hybrid-catalyst-coated LSF cell thus resulting in a double-side modified cell (with a CGO20coated Ni/YSZ fuel electrode and the hybrid-catalyst-coated LSF oxygen electrode).…”
Section: Performance and Durability Of Double-side Modified Cellmentioning
confidence: 99%